2014
DOI: 10.1186/s12875-014-0211-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of autologous platelet rich plasma for the treatment of vascular ulcers in primary care: Phase III study

Abstract: BackgroundVascular ulcers are commonly seen in daily practice at all levels of care and have great impact at personal, professional and social levels with a high cost in terms of human and material resources. Given that the application of autologous platelet rich plasma has been shown to decrease healing times in various different studies in the hospital setting, we considered that it would be interesting to assess the efficacy and feasibility of this treatment in primary care. The objectives of this study are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 14 publications
0
34
1
Order By: Relevance
“…PRP has been reported to be associated with numerous human diseases; in joint diseases, the application of autologous PRP has been observed to lead to decreased healing times in various clinical cases (28)(29)(30). In addition, a previous report suggested that the efficacy and feasibility of PRP treatment was notable in RA and avascular necrosis (31). However, although the application of PRP in the laboratory and in clinical practice has exhibited positive outcomes, the use of PRP has remained controversial, particularly its application as a treatment for RA and ankle cartilage pathology (32).…”
Section: Discussionmentioning
confidence: 99%
“…PRP has been reported to be associated with numerous human diseases; in joint diseases, the application of autologous PRP has been observed to lead to decreased healing times in various clinical cases (28)(29)(30). In addition, a previous report suggested that the efficacy and feasibility of PRP treatment was notable in RA and avascular necrosis (31). However, although the application of PRP in the laboratory and in clinical practice has exhibited positive outcomes, the use of PRP has remained controversial, particularly its application as a treatment for RA and ankle cartilage pathology (32).…”
Section: Discussionmentioning
confidence: 99%
“…Platelet rich plasma (PRP) is defined as a rich suspension of platelets in plasma derived from whole blood that has 2-6 fold higher platelet concentrate [26]. Platelets are a reservoir of proteins known as growth factors including platelet derived growth factor (PDGF), transforming growth factor-β (TGF-β), epidermal growth factor (EGF), vascular endothelial growth factor (VEGF), insulin like growth factor-1 (IGF-1), and fibroblastic growth factor (FGF).…”
Section: Discussionmentioning
confidence: 99%
“…(14)(15)(16) Several studies using this technique have demonstrated adecrease in healing time compared to conventional treatments (in particular, the currently recommended MWC). Releasing cytokines and hemostatic factors into the tissue of the growth factors, after the destruction of platelets, induces chemotaxis of the major cell types participating in the repair processes.…”
Section: Discussionmentioning
confidence: 99%